Implementation of Direct Cash Assistance in Improving the Welfare of the Pembantanan Village Community: تنفيذ المساعدة النقدية المباشرة لتحسين رفاهية مجتمع قرية بيمبانتان - Apifah, Nida Nor; Rusdiana; Hu’shila Awalia Rizqiani (Rayah Al-Islam, 2025)
The implementation of Direct Cash Assistance is a form of social protection scheme based on social assistance aimed at determining the implementation and effectiveness of Direct Cash Assistance in improving the welfare of the people of Pambanganan Village, to evaluate the suitability of the Direct Cash Assistance (BLT) program with Islamic economic principles in the context of improving the welfare of the people of Pambanganan Village. This study uses a qualitative approach with a type of field research that focuses on the implementation of direct cash assistance in Pambanganan Village with research subjects being beneficiary families and village officials. Data collection techniques used are observation and interviews with BLT beneficiary families. The technique for analyzing data uses descriptive analysis using the Triangulation method developed by Miles and Huberman. The effectiveness of the direct cash assistance program is assessed from 3 points, namely 1. Target accuracy, 2. Timeliness, 3. Accuracy of the amount. The results of the data obtained by the author in the field can be concluded that the achievement of welfare and happiness indicators according to QS Al-Quraish verses 3-4 a. Tawakkal with 92% b. Loss of hunger with 52%, c. Loss of fear with 80%. In accordance with the principles of mashlahah dharuriyah, especially in protecting lives and protecting property.